Water quality monitoring for heavy metal contamination associated with acid mine drainage at abandoned and active mining sites in Pahang - Madzin, Zafira; Mohd Kusin, Faradiella; Yusof, F. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Acid mine drainage is typically resulted from mining activities through mineral interactions with atmospheric oxygen and water. This study investigates the heavy metal concentrations and also occurrence of acid mine drainage (AMD) in active and abandoned mining sites in Pahang. Three sites were investigated within Kuantan (active bauxite mining), Kuala Lipis (active iron mining) and Bukit Ibam (abandoned iron mine). In-situ parameters were measured and surface water and sediment were also collected and analysed for heavy metals. Based on the investigations, there are sites that have acidic pH values indicating the occurrence of acid mine drainage (AMD) which has been a major concern of this study. Based on the heavy metal analysis, the concentrations of Fe, Mn, Al and Pb in water and sediment of few sites have exceeded the allowable standard limits for treated and raw water by the Malaysian Ministry of Health. The study concludes that there is an urgent need for appropriate treatment of the affected sites to prevent further environmental deterioration.